Pengolahan Limbah Cair Sawit Untuk Menyisikan TSS Menggunakan Chlorella Sp. Yang Diimmobilisasi Ca-Alginat Di Dalam Flat-Fotobioreaktor - Hasti, Fucy Adilla; Elystia, Shinta; Muria, Sri Rezeki (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Industry of palm oil continues to develop so that production of palm oil increases followed by increasing by-products in the form of waste. The biggest waste is Palm Oil Mill Effluent (POME) wastewater and needs to be treated because containing high organic matter. Utilization of microalgae carried out to wastewater treatment process. POME is used as a medium and nutrient for microalgae growth. Chlorella sp. immobilized with calcium alginate to remove of TSS parameter on POME. In this study, variations of wastewater concentration are 50%, 75%, 100% (v/v), and different source light i.e. artificial light and sunlight sources, and the contact times 0,1,3,5,7 (days ). Based on the results that Chlorella sp. able to growth well in a medium of 50% wastewater concentration using artificial lightsource on 7th days and removal efficiency of TSS obtained to 76.43%. Keywords: Palm Oil Mill Effluent, TSS Removal, Immobilization of Alginate, Flatphotobioreactor